PEMBINAAN PENGAMEN EKSENTRIK PADA KAWASAN PUBLIK KABUPATEN BANYUWANGI SEBAGAI UPAYA PERUBAHAN DARI KEMISKINAN MENUJU KESEJAHTERAAN - Wardah Rifkah Majidah; Safrieta Jatu Permatasari; Hary Priyanto (Nusantara Hasana Journal, 2025)
The existence of eccentric buskers has become a social problem that is simultaneously prevalent in Banyuwangi Regency. They carry out their activities in a different way from buskers in general, in terms of their appearance and character as silver humans, robots, clowns, or dance artists, including being different from their personal behavior when they are ordinary people. The efforts of eccentric buskers to capitalize on their misery have an impact on personal gain, while also disrupting the spirit of the Banyuwangi Regency Government in urban planning and empowerment programs that are just and prosperous. The research is based on a qualitative descriptive approach. The purpose of the research is to describe and analyze the role of the Banyuwangi Regency Social Service, Women's Empowerment and Family Planning in dealing with eccentric buskers in Banyuwangi Regency. The conclusion of the research is that the Banyuwangi Regency Government through the Social Service, Women's Empowerment and Family Planning has made efforts to deal with eccentric buskers through empowerment policies and programs in order to improve welfare, maintain public order, and eliminate negative stigma from society. Research recommendation, Social Service, Women Empowerment and Family Planning of Banyuwangi Regency in implementing the program needs a holistic approach and cross-sector collaboration, so that eccentric buskers are able to escape the cycle of poverty, and do not return to activities in public areas illegally.